Experimental and Numerical Study of Desalination Using Solar Energy and Phase Change Materials - Reyes-Salinas, A; Henriquez-Vargas, L; Pailahueque-Barahona, N; Gatica-Candia, E (Elsevier Ltd, 2023)
The present work experimentally desalinate water and model a passive solar desalinator of 0.55 m2 that uses phase change materials (PCM), assessing the effects of storing energy in 4.5 kg of coconut oil or paraffin wax contained in copper tubes, and the mass of water in the container (5.55, 8.25 and 11.0 kg), on the unit performance. The experiments carried out in Santiago de Chile allowed to obtain condensate masses between 3.2 and 4.3 kg/m2 per batch with a temperatures between 23 and 83∘C for the absorber plate and 21–77∘C for the glass. Annual water production ranged from 1120 to 1313 liter/m2, with costs between 0.0165 and 0.0593 $/liter. PCM incorporation had no impact on production as the exposed area is shared between absorber plate and tubes. To better evaluate the effect of the parameters studied, results are presented as the ratio between the mass of condensate and the solar energy received, which gives independence from the solar irradiation variability and allowed to identify a slight superiority in the productivity of condensate using coconut oil. The model developed and coded in MATLAB, including PCM and the effect of self-shading, adequately predicts the mass of condensate and phase temperatures (water, glass and PCM) with a mean root mean square error of 0.03 kg and 1.9∘C respectively. The model is characterized by a low computation time and a high level of prediction for the condensate mass. © 2023 Elsevier Ltd
Keywords: Desalination; PCM; Solar energy; Solar still; Modeling